CSR COMMUNICATION STRATEGIES FOR THE ECONOMIC RESILIENCE OF COASTAL COMMUNITIES - Priyo Bayu Utomo; Denik Iswardani Witarti (LPPM Stikosa - AWS, 2026)
This study aims to analyze communication strategies Corporate Social Responsibility (CSR) in supporting the economic resilience of coastal communities in Tarumajaya District. Tarumajaya District was chosen as the research location because it is a coastal area with a high level of economic dependence on marine resourcebased micro-enterprises and is vulnerable to income fluctuations and coastal environmental pressures. This study used a qualitative approach with a case study design. Researchers collected data through field observations, in-depth interviews with micro-enterprises, village officials, and CSR program facilitators, as well as analysis of activity report documents and related publications. The research results show that a participatory, dialogic, and contextual CSR communication strategy can improve community financial literacy, encourage the emergence of new businesses based on local potential, and strengthen digital marketing capabilities through the use of social media. A communication strategy that emphasizes two-way interaction, hands-on practice, and ongoing mentoring has proven effective in driving changes in the economic behavior of coastal communities. This research provides practical contributions for governments, companies, and universities in designing more effective and sustainable CSR communication strategies for the economic empowerment of coastal communities